Respon Pertumbuhan dan Hasil Tanaman Sawi Hijau (Brassica juncea L.Var. Tosakan) Dengan Perbedaan Media Tanam Organik dan Penambahan Pupuk Organik Limbah Sludge Kertas di Dataran Rendah - Riska Nurlaela; Muharam Muharam; Rika Yayu Agustini; Devie Rienzani Supriadi (Peneliti.net, 2021)
The research was carried out at the Screen House of the new land of UNSIKA, Pasir Jengkol Village, Majalaya District, Karawang Regency, from October 2020 to March 2021. The design used was a non-factorial Randomized Block Design (RBD) with 6 treatments and 4 replications, namely A (cocopeat with paper sludge organic fertilizer 1:0), B (husk charcoal with paper sludge organic fertilizer 1:0), C (cocopeat with paper sludge organic fertilizer 3:1), D (husk charcoal with paper sludge organic fertilizer 3:1 ), E (cocopeat 1:1 organic fertilizer paper sludge), F (husk charcoal 1:1 organic fertilizer paper sludge) so that there were 24 experimental units. The results showed that the addition of organic planting media and organic sludge fertilizer had a significant effect on mustard plants aged 4 weeks after planting, with a plant height of 30.32 cm in treatment D. Meanwhile, on the observation of leaf area, the addition of planting media in organic sludge fertilizer had a significant effect on mustard plants with an area of ​​447.725 in treatment F. The combination of organic growing media and organic sludge fertilizer gave a significant effect on root length of 30.05 cm in treatment F. Organic planting media and sludge fertilizer had a significant effect on wet weight 1055.75 grams and the wet weight without roots is 93.75 grams.